Evaluating The Effect Of Mindfulness-Based Training Programs On Reducing Burnout Among Emergency Department Nurses (The Review of Diabetic Studies, 2025)
Background: Emergency department (ED) nurses operate in high-stress, unpredictable environments, placing them at significant risk of occupational burnout—characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. Burnout not only impacts nurse well-being but also threatens patient safety and care quality. Mindfulness-based interventions (MBIs) have shown promise in reducing stress and burnout in healthcare settings, yet there is a need for targeted research within the unique context of emergency nursing.Methods: This quasi-experimental study utilized a pre-test/post-test design to evaluate the effects of an eight-week mindfulness-based training program on burnout levels among ED nurses. A purposive sample of 120 registered nurses participated in weekly 90-minute sessions incorporating guided meditation, breathing exercises, and reflective practices. Burnout was measured using a validated questionnaire assessing emotional exhaustion, depersonalization, and personal accomplishment. Data were collected before and after the intervention and analyzed using paired sample t-tests.Results: Following the intervention, significant reductions in burnout were observed across all dimensions. High emotional exhaustion decreased from 41.7% to 12.5%, high depersonalization from 25% to 12.5%, and low personal accomplishment from 25% to 8.3%. Mean scores for emotional exhaustion (28.5 to 19.3), depersonalization (16.2 to 10.8), and personal accomplishment (31.0 to 38.6) showed statistically significant improvements (p < 0.001 for all).Conclusion: The mindfulness-based training program effectively reduced burnout among ED nurses, enhancing emotional resilience and professional fulfillment. These findings support the integration of structured mindfulness interventions into nurse support programs to mitigate burnout, improve well-being, and promote a more resilient emergency care workforce.